Reliability of tumour grade 1 and endometrioid cell type on preoperative endometrial biopsy. (January 2015) - Baek, M.-H.; Park, Y.-R.; Suh, D.-S.; Lee, S.-W.; Park, J.-Y.; Kim, D.; Kim, J.-H.; Kim, Y.-M.; Kim, Y.-T.; Nam, J.-H.
Abstract The aim of this study was to evaluate the reliability of using tumour grade and cell type on preoperative endometrial biopsy for the selection of patients for conservative hormone treatment. We retrospectively reviewed results of 643 patients with endometrial carcinoma for tumour grade and 817 for tumour cell type who underwent endometrial biopsy followed by surgery. Of the 357 patients with a grade 1 tumour on preoperative endometrial biopsy, 58 (16.2%) were upgraded based on a final pathology report from hysterectomy specimens. For grade 1, the preoperative endometrial biopsy showed a sensitivity of 80.4%, a specificity of 78.6%, a positive predictive value (PPV) of 83.8% and a negative predictive value (NPV) of 74.5%. Of the 672 patients with the endometrioid cell type on preoperative biopsy, 46 (5.6%) showed a different cell type on final pathology. For the endometrioid cell type, preoperative endometrial biopsy had a sensitivity of 91.3%, a specificity of 64.9%, a PPV of 93.2% and an NPV of 58.6%. This weak predictive value should be considered when selecting patients for conservative hormone treatment.